Can computer models be used for social learning? A serious game in water management. (January 2016) - Van der Wal, Merel M.; de Kraker, Joop; Kroeze, Carolien; Kirschner, Paul A.; Valkering, Pieter
Abstract: Computer simulation models are increasingly used to support solving complex problems in natural resource management, with social learning as subsidiary goal of the solution process. In this research, a serious game on water management is used where participants receive feedback on consequences of their choices from an Integrated Assessment Meta Model. This study aims to determine if and how social learning takes place and explores the role of the model in social learning. Group discussions were qualitatively analysed to uncover and understand the mechanisms in this process. Results show that social learning took place in 10 of the 12 game sessions. Though model feedback was an important driver for social learning, social learning was driven most by the team's reflection on their perspective. We conclude that using a model can facilitate social learning in a serious-game setting, in particular in combination with reflection on teams' perspectives. Highlights: We explored the role of a computer model in social learning on water management. Group discussions were qualitatively analysed to understand the role of the model. Model feedback was an important driver of social learning. Social learning was driven most by reflection by people on their perspectives.